PENGARUH KUALITAS LAYANAN DAN AKUNTABILITAS PENGELOLAAN DANA ZAKAT PADAÂ LEMBAGA AMIL ZAKAT TERHADAP LOYALITAS MUZAKKI - TARAFERUATIE TAUFIK, AIZALIA (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this study is to determine the effect service quality at Amil Zakat Institute regarding on the lack of realization of zakat acceptance and to analyze the effect of accountability of zakat fund management on the obedience of muzakki for zakat. This study uses purposive sampling technique, and the final sample is 150 muzakki. Using SEM analysis and smart-PLS (Partial Least Square) software, this study finds that service quality and accountability have significant influence on muzakki loyalty. Keyword: accountability, muzakki loyalty, quality of service.